Cryptic Zooplankton Diversity Revealed by a Metagenetic Approach to Monitoring Metazoan Communities in the Coastal Waters of the Okhotsk Sea, Northeastern Hokkaido - Hirai, Junya; Katakura, Seiji; Kasai, Hiromi; Nagai, Satoshi (Frontiers in Marine Science, 2017)
Monitoring zooplankton communities is important to understand dynamics in marine ecosystems. However, it is difficult to identify cryptic species and immature stages of zooplankton using morphological classification, which is time-consuming and requires high skill levels. Here, we conducted a metagenetic analysis of the 18S region in 101 zooplankton samples collected weekly throughout 2014 and 2015 at the Okhotsk Tower in Mombetsu, Hokkaido, Japan, and compared the results of this analysis with those provided by morphological analysis. The metagenetic analysis detected 561 molecular taxonomic units (MOTUs), whereas the morphological analysis detected 201 taxonomic groups. Zooplankton communities were dominated by copepods throughout the sampling period; however, non-copepod taxa, which comprised high proportions of both MOTUs (mean 51.1%) and sequence reads (mean 19.1%), were also important. Cryptic diversity detected by the metagenetic analysis was primarily driven by Copepoda and by the larvae of benthic taxa such as Bivalvia, Gastropoda, and Polychaeta. Community structure and diversity varied between periods of warm and cold water, indicating strong correlations with water temperature and thus seasonality. Furthermore, metagenetic analysis revealed detailed seasonal changes in dominant taxa, including larval stages of metazoans with high taxonomic resolutions; these included commercially important organisms such as Japanese scallops. The metagenetic analysis revealed that changes in both water mass and bentho-pelagic interactions sustain ecosystems rich in zooplankton diversity in this area. Metagenetic analysis provides novel insight into zooplankton diversity, and generates massive sequence data that may be used in future research; thus, it is considered an effective tool for monitoring zooplankton communities.